Shelf-Life Analysis, Nutritional Quality, and Raw Material Sourcing of Chayote (Sechium edule (Jacq.) Swartz)-Enriched Broiler Chicken Dimsum - Dewi Yunita; Yuliani Aisyah; Eva Murlida; Siti Safira Kusuma; Ariva Mayzuhra (Animal Husbandry Department, The Faculty of Agriculture, Universitas Syiah Kuala, 2026)
Dimsum is a popular snack in Indonesia and is widely available in Banda Aceh. However, it has a limited shelf-life. This study was conducted in three stages. In the first stage, the primary objective was to determine the shelf life of raw and steamed broiler chicken Dimsum made with chayote, referred to as CCD, when stored at different temperatures (ambient, chilled, and frozen). The study observed pH values, moisture content, total plate counts (TPC), and total counts of Salmonella spp. and Staphylococcus aureus. The study indicated that raw CCD lasts for one hour at room temperature, whereas steamed CCD lasts for only 4-8 hours. Both types of CCD can be stored for 1-2 days in chilled storage and 1-2 weeks in frozen storage. Steamed CCD meets Indonesian quality standards for chicken nuggets (SNI 6683:2014). The CCD is also high in protein (17.38%), fiber (4.54%), and antioxidants (12.65%). In the second stage, a comparative study was conducted between CCD and Dimsum from three different outlets in Banda Aceh. The results showed that CCD had the highest fiber content among the samples tested. The final stage of this research aimed to identify modern markets for sourcing broiler chicken meat as a raw material for CCD production. The results suggest that the M1 modern market is suitable for purchasing chicken broilers for use as a raw ingredient for Dimsum.